Green storytelling marketing: influencing consumer purchase decision through environmental consciousness - Anastasia Pratiwi Lauwrensia; Angga Ariestya (Fakultas Ilmu Komunikasi Universitas dr. Soetomo, 2022)
This research is useful for the development of marketing communication science. In addition to academic benefits, this research also plays a role in strengthening the green marketing industry which emphasizes environmental sustainability in its marketing activities. This research uses a quantitative method for followers of the Instagram account @Sustaination (N=338). Participants are account followers who have purchased composter products and carried out composting activities. The results show that green storytelling marketing activities can have a direct influence on purchasing decisions for composter products. In addition, the influence of green storytelling marketing can also effect on purchase decision through environmental consciousness. This is because green storytelling marketing can affect the affective, cognitive, and dispositional dimensions of environmental consciousness. In green storytelling marketing, there is information and knowledge conveyed through the stories displayed. This can then help influence the active dimension in which there is an element of purchasing green products. This is the reason green storytelling marketing through environmental consciousness can influence the purchase decision of composter products.